Safety evaluation of HOWARU® Restore (Lactobacillus acidophilus NCFM, Lactobacillus paracasei Lpc-37, Bifidobacterium animalis subsp. lactis Bl-04 and B. lactis Bi-07) for antibiotic resistance, genomic risk factors, and acute toxicity. (December 2017) - Morovic, Wesley; Roper, Jason M.; Smith, Amy B.; Mukerji, Pushkor; Stahl, Buffy; Rae, Jessica Caverly; Ouwehand, Arthur C.
Abstract: Although probiotic lactobacilli and bifidobacteria are generally considered safe by various regulatory agencies, safety properties, such as absence of transferable antibiotic resistance, must still be determined for each strain prior to market introduction as a probiotic. Safety requirements for probiotics vary regionally and evaluation methods are not standardized, therefore methodologies are often adopted from food ingredients or chemicals to assess microbial safety. Four individual probiotic strains, Lactobacillus acidophilus NCFM ®, Lactobacillus paracasei Lpc-37 ®, Bifidobacterium animalis subsp. lactis strains Bl-04 ®, and Bi-07 ®, and their combination (HOWARU ® Restore) were examined for antibiotic resistance by broth microdilution culture, toxin genes by PCR and genome mining, and acute oral toxicity in rats. Only B. lactis Bl-04 exhibited antibiotic resistance above a regulated threshold due to a tetW gene previously demonstrated to be non-transferable. Genomic mining did not reveal any bacterial toxin genes known to harm mammalian hosts in any of the strains. The rodent studies did not indicate any evidence of acute toxicity following a dose of 1.7–4.1 × 10 12  CFU/kg body weight. Considering a 100-fold safety margin, this corresponds to 1.2–2.8 × 10 12  CFU for a 70 kg human. Our findings demonstrate a comprehensive approach of in vitro, in silico, and in vivo safety testing for probiotics. Highlights: Safety evaluations of individual probiotics are equivalent to combined products. In vitro and in silico testing sufficiently identifies microbial safety risks. In vivo toxicology studies of typical probiotic genera may not be necessary.